Successful Coronary Protection during TAVI in Heavily Calcified Aortic Leaflets in Patient with Short and Low Left Coronary System - Mohamad Kabach; Abdulah Alrifai; Lawrence Lovitz; Mark Rothenberg; Cristiano Faber; Marcos Nores (Case Reports in Cardiology)
Transcatheter aortic valve replacement has been recently approved for patients who are high or intermediate risk for surgical aortic valve replacement. The procedure is associated with several known complications including coronary related complications. Coronary obstruction is rare but disastrous complication, and it is associated with a high mortality rate. Coronary protection technique has emerged as a preemptive technique to avoid this complication. We present a case of successful coronary protection during TAVR in severely calcified left cusp in patient with short and low left ostium.